Las formas de las represalias violentas en Argentina. Las acciones colectivas de violencia punitiva (2009-2015) (Delito y Sociedad, 2018)
This article analyzes the evolution of collective actions of punitive violence in Argentina during the period 2009-2015 and describes the different ways in which they occur. Based on the statistical processing of a database built with all the episodes recorded in both national and local press, we can make two assertions. First, the collective actions of punitive violence in Argentina have grown in recent years. Second, based on the attributes of this collective actions, we can define 3 distinctive pattern or classes. The hypothesis of the work argues that the increase of these actions is related to the transformations in collective action in recent Argentina, specifically the installation of collective violence as a performance inscribed in the repertoire of grasroots protests and the consolidation of demand for justice along with claims against impunity as one of the most popular demands. From the point of view of the forms, the article shows the three types of collective actions of punitive violence: lynchings, attacks and outburts.
Keywords: Lynching; outbursts; collective action; collective violence; punitive violence